Role of Topical Calcipotriol to Potentiate the Effect of Photochemotherapy (PUVA) in Treatment of Vitiligo - Ahmed, Moyassaque; Khan, Abdul Latif; Alam, Md Shakibul; Wahab, Md Abdul (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Vitiligo is a specific, common, often heritable acquired disorder characterized by well-circumscribed milky white cutaneous macules and patches devoid of identifiable melanocyte. Treatment of vitiligo, though quite frustrating, includes repigmentation therapies like Topical glucocorticoids, Topical calcipotrieinene, Topical PUVA (Psoralen + Ultraviolet Light A). The combination of calcipotriol and PUVA proves quite effective for management of this condition. Objectives: To compare the effectiveness of PUVA and the combination of topical calcipotriol and PUVA in treatment of vitiligo. Materials and Methods: This quasi experimental study was undertaken at Combined Military Hospital, Dhaka Cantonment, Dhaka from March to October 2015. A total of 32 patients suffering from vitiligo diagnosed clinically and confirmed by Wood’s lamp examination were selected as study population. Systemic PUVA, thrice weekly was given but Topical calcipotriol applied twice daily at one side of the body and other side used nothing Topically. Response was assessed clinically every 4 weeks along with photographic record and compared between two sides of the body. Results: During the course of the treatment, the calcipotriol plus PUVA treated side showed considerably better improvement than only PUVA treated side. The response was Excellent; 37.8% (12/32), Good; 31.3% (10/32), Fair; 18.8% (6/32), Poor; 12.5% (4/32) in calcipotriol plus PUVA treated side whereas Excellent; 12.5% (4/32), Good; 25% (8/32), Fair; 43.8% (14/32) and Poor; 18.8% (6/32) in only PUVA treated side. Conclusion: This study shown that concurrent topical calcipotriol potentiates the efficacy of PUVA in the treatment of vitiligo along with the fact that this combination achieves earlier pigmentation with a lower total UVA dosage in comparison to only PUVA therapy. JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 23-25